2019
DOI: 10.1017/s0033291719001387
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of conditioning, extinction learning, and extinction recall in posttraumatic stress disorder: a meta-analysis of functional magnetic resonance imaging studies

Abstract: BackgroundEstablishing neurobiological markers of posttraumatic stress disorder (PTSD) is essential to aid in diagnosis and treatment development. Fear processing deficits are central to PTSD, and their neural signatures may be used as such markers.MethodsHere, we conducted a meta-analysis of seven Pavlovian fear conditioning fMRI studies comparing 156 patients with PTSD and 148 trauma-exposed healthy controls (TEHC) using seed-based d-mapping, to contrast neural correlates of experimental phases, namely condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 73 publications
3
65
1
1
Order By: Relevance
“…CS-activity was predominantly observed in the anterior insula. Anterior insula activation during extinction could reflect persistent learned threat-cue reactivity surviving from acquisition and is well in agreement with studies showing central autonomicinteroceptive network activity during fear acquisition (29) as well as fear extinction (30) and is also in agreement with a meta-analysis demonstrating insula hyperactivity during extinction learning in patients with PTSD (28). The absence of differential amygdala activation during extinction in the current study could point to a swift intensity reduction of CS1 response during extinction (43) that could have been enhanced by a procedural shift (i.e., reinforcement of both CS1 and CSby film clips) during acquisition, followed by complete film US absence during extinction.…”
Section: Individual Fear Extinction Predicts Intrusive Memoriessupporting
confidence: 90%
See 1 more Smart Citation
“…CS-activity was predominantly observed in the anterior insula. Anterior insula activation during extinction could reflect persistent learned threat-cue reactivity surviving from acquisition and is well in agreement with studies showing central autonomicinteroceptive network activity during fear acquisition (29) as well as fear extinction (30) and is also in agreement with a meta-analysis demonstrating insula hyperactivity during extinction learning in patients with PTSD (28). The absence of differential amygdala activation during extinction in the current study could point to a swift intensity reduction of CS1 response during extinction (43) that could have been enhanced by a procedural shift (i.e., reinforcement of both CS1 and CSby film clips) during acquisition, followed by complete film US absence during extinction.…”
Section: Individual Fear Extinction Predicts Intrusive Memoriessupporting
confidence: 90%
“…Furthermore, the neural pathophysiology proposed by neuroscientific models of PTSD has also been linked to increased fear acquisition and deficient extinction learning (23). In patients with PTSD compared with trauma-exposed healthy control subjects, fear acquisition and extinction learning have been related to the insula, dACC, and amygdala (28). However, in healthy subjects, fear acquisition (29) and extinction learning (30) have particularly been linked to brain regions implicated in threat appraisal-the anterior insula and dACC-but without consistent findings for the amygdala or VMPFC.…”
mentioning
confidence: 99%
“…Although they arise from thalamic circuits, corticothalamic feedback projections and divergent connectivity between thalamic and cortical neurons are essential for establishing the long-range synchronization of spindles ( Beenhakker and Huguenard, 2009 , Contreras et al, 1997 ). Evidence suggests that thalamic dysfunction is partly involved in the etiology of PTSD ( Kim et al, 2007 , Lanius et al, 2006 , Suarez-Jimenez et al, 2019 ). Moreover, the functional connectivity between the thalamus and cortical regions has been shown to be altered in PTSD during script-driven imagery ( Lanius et al, 2005 ) and in the resting state ( Terpou et al, 2018 , Yin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Lis et al (2019) concluded a crucial role for compromised expectation with subsequent overgeneralization of threat and undergeneralization of safety signals from fear‐potentiated startle and subjective measures, other articles used structural and functional brain imaging to identify predictors of PTSD susceptibility. Resting‐state network connectivity and activity in response to fear or trauma‐related stimuli in the hippocampus, amygdala, insula, and prefrontal cortex have been found to predict PTSD in trauma‐exposed individuals (e.g., see overviews by Suarez‐Jimenez et al, 2019; Dretsch et al, 2016). In the present volume, Sambuco et al (2019) suggest that post‐traumatic stress, related affective psychopathology, and trauma exposure, when considered transdiagnostically, may confer a risk for emotional hyporeactivity: fMRI was monitored while patients with different anxiety and mood disorders viewed emotional and neutral scenes.…”
mentioning
confidence: 99%